Quo vadis the Catholic Church and the Zimbabwe Council of Churches? Exploring the ‘Mine Is Right’ Dilemmas in the Path to Christian Unity in Zimbabwe - Canisius Mwandayi; Theresa Mugwidi (Palgrave Macmillan, Cham, 2022)
This chapter focuses on the interaction between the Catholic Church and the Zimbabwe Council of Churches (ZCC). Its central argument is that both the Catholics and the Protestants need to change their attitudes towards each other. When they adopt the right attitude and collaborate, they can achieve better results. The chapter explores the historical context that has generated tension between Catholics and Protestants. However, the authors are convinced that by joining forces, the two can work more effectively to enhance development in Zimbabwe.